MOTIVASI KERJA APARATUR SIPIL NEGARA DI KANTOR KECAMATAN PELING TENGAH KABUPATEN BANGGAI KEPULAUAN - Malonta, Rutdiansy (Katalogis, 2018)
The purpose of this research is to know work motivation of the civil state apparatus in Central Peling subdistrict office of Banggai Kepulauan regency. Type of this research is a descriptive qualitative approach which was obtained from the deep interviews result. The location of this researchwas located in Central Peling sub district office of Banggai Kepulauan regency. As much as 5 (five) persons civil state apparatus was selected purposively as the informants of the research. With data sources were including primary data and secondary data and techniques of data collection which was through observation, interviews, and documentation. By using the Interactive model of data analysis Miles and Huberman (2007:20). The theory that be used was a theory which stated by McClelland that is there are 3 indicators of work motivation, they are achievement needs, power needs and affiliation needs. The results of the work motivation of the civil state apparatus in Central Peling subdistrict office of Banggai Kepulauan had been said good overall, this was indicated through 3 aspects of work motivation, it was achieving needs, as long as this time the employees had been motivated to work well in carrying out their duties and responsibilities because of the existence of a desire to ful fill their need of achieving to get good recognition from the boss or partners and from the employees it selves. An indicator of power needs was ran well, because most employees are motivated to work to get higher position behind his/her devotion as a man of the society, but for the most employees, the power needs is not a motivation to improve performance, as well as the needs of affiliated are already well, because all this time the relationship of cooperation had been harmonized in order to achieve the purpose of Central Peling subdistrict office of Banggai Kepulauan regency.